The quality gap in Chile’s education system - José Luis Drago; Ricardo D. Paredes (CEPAL Review, 2011)
The quality gap in education between Chilean schools with different administrative structures (especially in the case of municipal schools and private subsidized schools) has long been a subject of analysis and discussion within the wider debate surrounding the relative efficiency and role of public education. Unconditioned differences in the results of standardized tests that point to higher levels of quality in private schools diminish when sociodemographic factors are controlled for, but the question as to what control variables should be used and which methodology is the most appropriate, as well as the extent of the reduction, all continue to be a subject of debate. Here we undertake a meta-analysis of 17 of the main studies that have been done on the subject. The analysis shows how sensitive the results are to the controls and estimation methods that are used. In the aggregate, private subsidized schools score approximately four points higher than municipal schools do. This is a statistically significant and educationally relevant differential.